Facing the Nazi Past: Silence, Memory and Inhabiting Responsibility. Issue 1 (2nd January 2020) - Frie, Roger
ABSTRACT: This article considers how history flows through us in ways that are both conscious and unconscious and examines the effects of the Nazi past and the Holocaust into the present. I maintain that individual experience is always permeated by the memories and narratives of those who came before us and that even when the past is shrouded in silence, we are confronted with its meanings and consequences. Using my own German family history as the site of exploration, I examine the dissociative processes at work in the transfer of memory from one German generation to the next. As a German descendant I address the obligations of memory and consider what it means to "inhabit responsibility" following the discovery of an unspoken Nazi past my family.